Resistance to Termites and Colour Change in Gombong Bamboo (Gigantochloa pseudoarundinacea) Modified with Boron Compounds, Vegetable Oil, and Heating - Lilih Cipta Pangestu; Trisna Priadi; Yanico Hadi Prayogo (Department of Forestry, Faculty of Agriculture, University of Lampung, 2026)
Bamboo is a potential material in the furniture, construction, and craft industries due to its rapid growth and good physical and mechanical properties. However, its vulnerability to attacks by wood–destroying organisms, particularly termites, necessitates preservation to extend its service life. This study evaluated the resistance of gombong bamboo to subterranean and drywood termites, as well as its color changes. The modification treatments involve boric acid equivalent (BAE) impregnation, heat treatment (60 °C, 150 °C, and 180 °C), and vegetable oils (linseed and neem oil). Statistical analysis using one-way ANOVA was performed to determine the significance of each treatment factor on weight loss and colour parameters, followed by Duncan’s Multiple Range Test for mean comparison. In addition, color change and the chemical composition of the most effective oil treatment in terms of termite resistance were analysed using Gas Chromatography-Mass Spectrometry (GC-MS). The results showed that BAE, neem oil, and the combined treatments (BAE-vegetable oils) effectively improved bamboo resistance to both termite tests. The synergy between BAE impregnation, heat treatment (180 °C), and neem oil produced the highest level of termite resistance. Heat treatment at elevated temperatures also caused significant colour changes, particularly a reduction in brightness (L*) and an increase in dark brown tones attributed to thermal degradation of hemicellulose and extractives. GC-MS analysis revealed that neem oil was dominated by fatty acids and other compounds known for their antimicrobial, antifeedant, and termite-repellent activities, which likely contributed to the enhanced biological performance of the treated bamboo. Keywords: bamboo modification, bio-based treatment, impregnation, sustainable bamboo utilization